ScHuchEmania / AK Mohd Shahrin Nizam ... [et al.] - Nizam, AK Mohd Shahrin; Hazlin, Datu Mohd; John, Grace; Junus, Juliana; Mazni, Marhain (2014)
Based on our company business, we manage to overcome all the challenges through the starting of operating the business. Start from the company plan where we decided to open a shoe retailer as a business. Then we plan out the organizational plan to make sure all the employees manage to realize and do their responsible in the company. For the marketing plan, we selected the suitable target market to ensure our product in the company reliable for the customer to purchase it by making a best approach to the customer themselves. Operational in the business is planned properly for our company to manage to get the best quality of shoe and at the same time it gives satisfaction to the customer towards our product. Finally, the financial plan where we plan our budget and expenses carefully to avoid lose in our company business. As a manager, working together with other people makes us to get more experiences in the business. Hence, any challenges in the future by sure we will be ready to face and overcome together for the business to become successful.